Challenges and Strategies of EFL Students from Islamic Boarding School in Musical Drama - Addin, Hisan Nor; Amalia, Taranindya Zulhi (Journal Corner of Education, Linguistics, and Literature, 2025)
This study aimed to identify challenges and strategies in preparing an English musical drama performance by Islamic boarding school students as English as a Foreign Language (EFL). Data were collected through interviews, document analysis, and questionnaires. The results of the study indicate that there are linguistic challenges for participants, especially in terms of pronouncing dialogues and script texts that must be read fluently. In addition, students also face non-linguistic challenges outside of the language aspect that can have a significant impact on the preparation process, implementation, and final results of the performance. To overcome language barriers, guidance from educators, tiered exercises, intensive repetition, use of audiovisual references, and directed discussions are provided. Meanwhile, non-linguistic challenges were addressed through psychological support, optimal practice time management, application of a structured practice approach, and the use of video imitation techniques and creativity in adapting to resource limitations. Although there are still limitations, several strategies have proven effective. Overall, this drama performance is not only a medium for learning and showing off the students' learning outcomes, but also a means of instilling Islamic values ​​that are in line with the goals of Islamic boarding school education.